Philosophical understanding of Karl Popper and the theory of knowledge (Journal of Philosophy Culture and Political Science, 2015)
Karl Popper (1902-1994) the biggest philosophy of science of the twentieth century. He was a staunch opponent of all forms of skepticism, conventionalism and relativism in science, in human affairs, a staunch advocate of the «open society» and an implacable critic of totalitarianism in all its forms. One of the many outstanding features of Popper's philosophy - the scope of his intellectual influence. His works can be found social and scientific elements - the fundamental unity of philosophical vision and method. The philosopher best known for his work on the philosophy of science, as well as social and political philosophy, in which he criticized the classical concept of the scientific method, and vigorously defended the principles of democracy and social criticism, which he proposed to stick to allow the prosperity of an open society. Popper is the founder of the philosophical concept of critical rationalism. When all the modifications that have been subjected for half a century, the concept of the philosopher, it remained unchanged in the idea that the need, the possibility and necessity of criticism and constant revision of its provisions are basic and defining features of science, the existing scientific rationality. Each theory is vulnerable to criticism, otherwise it can not be regarded as scientific. If the theory is contradicted by the facts, it must be rejected. Karl Popper has made a great contribution to the development of the principles of scientific knowledge and became the founder of critical realism. Critical realism emerged as an attempt to solve the problems of philosophy Popper's demarcation (Department of scientific knowledge from unscientific) and induction (inductive reasoning admissibility of experience). In contrast, the principle of falsificationism Popper put forward the principle according to which the theory is scientific if there is a methodological possibility of its refutation by setting a particular experiment, even if such an experiment has not yet been put. In this paper we would like to follow those threads that bind together the philosophy of Popper, and to identify the relevance of the concept of Karl Popper for modern scientific thought and practice. The article is devoted to the philosophical understanding of the theory of knowledge and its interaction with modern society. The contribution of fallibilism to the establishment of Kazakh society.
Keywords: communication; modernity; fallibilism; falsifiability.